The Challenge of Women's Domestication Portrayed in Ayobami Adebayo's Stay with Me - Khodijah Munawar; Karina Hanum Luthfia (Universitas Islam Negeri Palopo, 2025)
This article explores the challenge of women’s domestication portrayed in Ayobami Adebayo’s Stay with Me, with a focus on how womanhood is narrowly defined through marriage and motherhood. Through the lens of Betty Friedan’s liberal feminism, this research analyses how societal and familial expectations and pressures domesticate women and reduce their identity and worth to their reproductive roles. The main character in this book, Yejide, represents a woman whose education, achievements, and personal identities are constantly overshadowed by pressures to bear children. This domestication and reduction of her womanhood not only limit her worth in the eyes of society but also gradually strip away her identity. This research reveals that by portraying her struggles and challenges, the novel critiques societal and familial norms that domesticate women and equate womanhood with motherhood. Ultimately, Stay With Me intervenes in the domestication of women and the reduction of womanhood to motherhood and demands a redefinition, one that recognises women as complete in themselves, regardless of whether or not they become mothers.